Práticas multimodais no aplicativo WhatsApp: apropriação da cultura escrita digital por crianças em processo de alfabetização - Rebecca Schirmer de Souza Vasconcelos (2019)
The writing culture is changing in the face of technological innovations, which leads us to investigate the functioning of digital writing culture in contemporary society. One of the main lies in the use of different applications, material supports and multimodal resources. In the range of social networks, the instant messaging application called WhatsApp prevails in Brazil. The purpose of this study was to investigate how WhatsApp practices, by children in the literacy process occur, aiming to understand their appropriation of the digital writing culture and the capacities they mobilize to read and produce multimodal texts in this environment. The methodology was a qualitative study, with data on uses and forms of learning reported in interviews and questionnaires, by children and their families, followed by an intervention via interaction between children and the researcher, through the exchange of messages in the application. The interaction strategy through the application aimed to verify how children use verbal written language and audio, as well as other semiotic resources in their conversations with the researcher. As for theoretical references, the research was based on different studies on digital writing culture, multimodality, literacy and digital literacy and interactivity. The analysis of the data collected showed ways in which children learned to use the application, either by observation or through the direct teaching from parents and relatives, the type of access to the material support, their preferences for usage and semiotic resources, such as audios, written messages, use of emoji, videos and images. By interacting through messages, children reveal pragmatic aspects of application usage, showcase knowledge of typical multimodality features of the screen, alternating or hybridizing languages for their functionality and for the production of meanings, and often their choices do not depend only on previous acquired reading and writing skills.